The Effect Of Aspect Ratio On Multi-Walled Carbon Nanotubes Filled Epoxy Composite As Electrically Conductive Adhesive - Sheikh Md Fadzullah, Siti Hajar; Nasaruddin, Muhamad Muaz; Kamalrudin, Massila; Ramli, Mizah; Mohamad, Imran Syakir; Omar, Ghazali; Akop, Mohd Zaid (Penerbit UTeM, 2019)
Multi-walled carbon nanotubes (MWCNTs) filled epoxy resin is a type of Electrically Conductive Adhesive (ECA) that is used as interconnect materials in electronics application. Carbon-based conductive adhesive usually has inferior electrical conductivity to silver but mechanically superior in terms of its bonding integrity. The aim of this paper is to study the effect of aspect ratio on the electrical and mechanical properties of the composite adhesive. The aspect ratio of the two types of MWCNT fillers are of 55.5 and 1666.5. The filler loading for both MWCNTs varies from 5wt.% to 12.7wt.%. From the experimental study, the sheet resistance for the ECA with higher aspect ratio is approximately 4.42kΩ/□ in comparison to only 44.86kΩ/□ for the ECA with lower MWCNT aspect ratio. Morphological analysis of the ECA showed evidence of MWCNT distribution in the ECA with different diameter size. Nonetheless, the MWCNTs filled epoxy with lower aspect ratio exhibit higher shear strength with a maximum value of 8.08MPa, in comparison to only 4.68MPa to that of the ECA with higher MWCNTs aspect ratio, possibly due to the tendency in forming agglomeration of the MWCNT with smaller tube diameter, resulting in weaker interfacial strength